Pengaruh Transformasi Digital Dan Keterlibatan Pegawai Terhadap Kinerja Pegawai Di Dinas Perkebunan Dan Peternakan Kabupaten Ogan Komering Ilir - Lidia Lidia; Sabeli Aliya (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
This study aims to examine the influence of digital transformation and employee engagement on employee performance. A quantitative approach with total sampling was used, involving 62 respondents. Data were obtained through questionnaires, observations, and interviews, then analyzed using multiple linear regression in SPSS. T-test results indicate that digital transformation (t = 3.625) and employee engagement (t = 9.343) have a positive and significant effect on employee performance. The F-test shows an F-value of 91.394 > F-table 3.15 with a significance level of 0.000, indicating that both variables simultaneously have a significant effect on performance. Digital transformation increases work efficiency and speed, while employee engagement strengthens motivation and responsibility. This study emphasizes the importance of synergy between technology implementation and active employee participation in improving the quality of public services